2019
DOI: 10.1021/acs.nanolett.9b00985
|View full text |Cite
|
Sign up to set email alerts
|

Approaching the Intrinsic Limit in Transition Metal Diselenides via Point Defect Control

Abstract: Two dimensional (2D) transition-metal dichalcogenide (TMD) based semiconductors have generated intense recent interest due to their novel optical and electronic properties, and potential for applications. In this work, we characterize the atomic and electronic nature of intrinsic point defects found in single crystals of these materials synthesized by two different methods-chemical vapor transport and self-flux growth. Using a combination of scanning tunneling microscopy (STM) and scanning transmission electro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
189
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 196 publications
(206 citation statements)
references
References 73 publications
10
189
0
Order By: Relevance
“…An appropriate use of high‐quality photonic and plasmonic cavities to alter the radiative recombination rate of excitons is key to tackling this limitation. Meanwhile, the development of high‐quality material growth methods and device fabrication techniques that do not compromise the emission properties of TMDs are essential. A comprehensive effort to understand the materials engineering, device physics, and exciton photophysics of 2D TMDs will be key to driving the future research toward the development of novel photonic devices.…”
Section: Discussionmentioning
confidence: 99%
“…An appropriate use of high‐quality photonic and plasmonic cavities to alter the radiative recombination rate of excitons is key to tackling this limitation. Meanwhile, the development of high‐quality material growth methods and device fabrication techniques that do not compromise the emission properties of TMDs are essential. A comprehensive effort to understand the materials engineering, device physics, and exciton photophysics of 2D TMDs will be key to driving the future research toward the development of novel photonic devices.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports of high concentrations of S vacancies [16,59] suggest that this is indeed a likely reason for the low experimental mobilities. Only recently have defect densities of n dis ∼ 10 11 cm −2 been demonstrated [47]. However, experimental transport properties of such high-quality TMDs have so far not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental STM studies on monolayer TMDs, atomic monovacancies have been found to be among the dominating sources of intrinsic lattice disorder [43][44][45][46][47][48]. Their stability and electronic structure have been studied in great detail theoretically [49][50][51][52][53][54][55][56][57], demonstrating that they often introduce in-gap states, as illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The positive sign can be attributed to the missing attractive core potential as well as unpaired σ electrons left at the vacancy site which yield an overall repulsive defect potential in Eq. (12). For the N substitutional in Fig.…”
Section: Graphenementioning
confidence: 99%
“…We start by discussing the impact of defects on the DOS, and in particular the defect-induced in-gap states observed in various STM/STS experiments. [10][11][12][13][14][15] Figure 7 shows the DOS for disordered MoS 2 (top) and WSe 2 (bottom) with different types of defects. The dashed vertical lines mark the position of the valence and conduction band edges (black) as well as the Fermi energy (E F ; red dashed line).…”
Section: A Dos and In-gap Bound Statesmentioning
confidence: 99%